2021
DOI: 10.3390/foods10112740
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Model Approach to Implement a Dynamic Shelf Life Criterion in Meat Supply Chains

Abstract: The high perishability of fresh meat results in short sales and consumption periods, which can lead to high amounts of food waste, especially when a fixed best-before date is stated. Thus, the aim of this study was the development of a real-time dynamic shelf-life criterion (DSLC) for fresh pork filets based on a multi-model approach combining predictive microbiology and sensory modeling. Therefore, 647 samples of ma-packed pork loin were investigated in isothermal and non-isothermal storage trials. For the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The study found that many meals were contaminated with high levels of bacteria, including S. aureus and E. coli. When meat products are exposed to significant levels of bacterial contamination, their characteristics are likely to change quickly [20,63,64]. The total bacteria count (TBC) is an indicator of hygienic quality and can also be used to assess the quality of food [30,65].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that many meals were contaminated with high levels of bacteria, including S. aureus and E. coli. When meat products are exposed to significant levels of bacterial contamination, their characteristics are likely to change quickly [20,63,64]. The total bacteria count (TBC) is an indicator of hygienic quality and can also be used to assess the quality of food [30,65].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, an IoT-based monitoring system can be used for getting insight into the current product status, performing weakness analysis on parameter profiles, and enhancing process control. Secondly, the combination of a monitoring system with predictive food models enables prediction of the remaining shelf life in each step of the chain on actual sensor data [ 112 ]. This approach facilitates optimization of storage and logistics [ 17 , 78 , 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, instead of the conventionally used FIFO (first in first out) principle, the FEFO (first expired first out) principle could be applied in warehouse management, which allows for shelf life-driven distribution of products [ 17 ]. To realize this, shelf life models for respective products are required [ 112 , 114 ]. If fresh fruit and vegetable supply chains should benefit from the combined use of IoT-based sensors and dynamic shelf life, a range of specific and accurate models is needed.…”
Section: Discussionmentioning
confidence: 99%